137 foto's gemaakt voor het boek "Het rijke onvermogen. Een fotoreportage over West-Duitsland" (201/118) - Alphen, Oscar van,
137 foto's gemaakt voor het boek "Het rijke onvermogen. Een fotoreportage over West-Duitsland" (201/118).